Mid-infrared laser operation of (Er0.07La0.10Y0.83)2O3 sesquioxide ceramic. (1st April 2023) - Balabanov, Stanislav; Loiko, Pavel; Basyrova, Liza; Permin, Dmitry; Kosyanov, Denis; Evstropov, Timofey; Filofeev, Sergey; Braud, Alain; Camy, Patrice
Abstract: A transparent sesquioxide ceramic (Er0.07 La0.10 Y0.83 )2 O3 was fabricated by vacuum sintering at 1780 °C for 3 h with lanthana acting as a sintering additive. It was of single-phase nature (sp. gr. Ia 3 ˉ ) with a close-packed microstructure (average grain size: 17 μ m, pore content: 5 ppmv) and high transparency of 80% at 1.1 μ m. The La 3+ ions induced additional inhomogeneous broadening in the absorption and emission spectra of Er 3+ ions. For the 4 I11/2 → 4 I13/2 transition, the stimulated-emission cross-section σ SE was 1.06 × 10 −20 cm 2 at 2719 nm and the luminescence lifetimes of the 4 I11/2 / 4 I13/2 states amounted to 2.73/5.91 ms, respectively. A (Er0.07 La0.10 Y0.83 )2 O3 ceramic laser generated 300 mW at 2840 nm with a slope efficiency of 27.7% and a laser threshold of only 17 mW.